Pleistocene evolution of Ninnis and Cook glaciers (East Antarctica) from a micropaleontological and sedimentological study: Preliminary result - Torricella, Fiorenza; Andò, Sergio; Battaglia, Francesca; Caburlotto, Andrea; Colizza, Ester; Crosta, Xavier; De Santis, Laura; Etorneau, Johan; Gallerani, Andrea; Gentz, Torben; Leventer, Amy; Macrì, Patrizia; et al. (2024)
The Cook Ice Shelf and Ninnis Glacier drain a large part of the Wilkes Land Basin, which contains the equivalent of about 4 metres of sea level. The glaciers in this region are thought to have retreated during the warm climatic phases of the Pleistocene, but the extent of the retreat and the identification of the driving forces are still controversial. The aim of this study is to contribute to the understanding of regional depositional processes and environmental conditions that shed light on the dynamics of the ice sheet and the factors that determine its stability and instability (ocean and atmospheric temperature and precipitation), and ultimately to refine the projected evolution of these glaciers. We here present the preliminary results of a multidisciplinary study (textural analyses, geochemical, chemical and petrographic analyses, paleomagnetic and micropaleontological determinations) carried out on six sediment cores collected on the continental slope off the Cook Ice Shelf and Ninnis Glacier in the framework of the Programma Nazionale di Ricerca in Antartide - PNRA project COLLAPSE ("Cook glacier-Ocean system, sea LeveL and Antarctic Past Stability'). We are currently documenting sedimentological processes and oceanographic conditions in this region during the Late Pleistocene. We identified three main units: the first unit consists of laminated silt with low microfossil content and is interpreted as influenced by bottom current; the second unit is a massive silt with ice debris, and very low microfossil content and is interpreted as indicating a period with intense ice calving with iceberg production; the third unit is a bioturbated mud with high microfossil content. The microfossil content, especially the diatoms, suggest that this unit is deposited during a period of open water.